Auguste Comte and the religion of humanity : the post-theistic program of French social theory - Wernick, Andrew (Cambridge University Press, 2001)
Andrew Wernick provides the first in-depth critique of Comte's concept of religion and its place in his thinking on politics, sociology and philosophy of science. Wernick relates Comte to Marx and Nietzsche and examines key features of modern and postmodern French social theory, tracing the inherent flaws of Comte's system.